Infectious risk profile and strategies for prevention and control of outbreaks in refugee, asylum seekers and migrant populations in EU/EEA countries: a systematic narrative review of evidences - Bianchi, Francesco Paolo; Fiacchini, Daniel; Frisicale, Emanuela Maria; Gili, Renata; Greco, Stefano; Guicciardi, Stefano; Riccò, Matteo; Zichichi, Salvatore; Zotti, Nunzio; Tafuri, Silvio (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. The recent surge in migration to and within the European Union and European Economic Area has brought the development of migration policy, including health policy, to the forefront of regional priorities. While migrants, in general, do not pose a health threat to the host population, specific subgroups of migrants, including refugees, asylum seekers, and irregular migrants, are particularly vulnerable to infectious diseases. To support public health policies in this area, the Emergency Preparedness and Management’ working group of the Italian Society of Hygiene, Preventive Medicine and Public Health has conducted a systematic narrative review with the aim to comprehensively analyze the infectious disease risk within the refugee and asylum seeker populations in EU, EEA, and EU-applicant countries. Methods. Forty-two studies were systematically selected from scientific articles in the MEDLINE/PubMed database from January 1, 2008, to June 1, 2023. The infectious risk associated with each infectious disease among refugees and [...]